Dynamický pyramidový rozklad ukazatele ROE - Ďurišová, Jana; Myšková, Renáta (Univerzita Pardubice, 2010)
As a lack of financial control is often a quick path to business failure, owners and managers often wonder how to improve return they are getting from their companies. Ratio analysis provides loads of information that is useful to regard. In our paper we focus attention on Return on Equity (ROE) indicator as we consider ROE under DuPont decomposition as one of the most appropriate measures of financial performance. We also point out possibilities of its application in practice. The aim of article is time evolution (2006 - 2009) of ROE indicator in selected automotive companies using functional method. Results of the analysis will show impact (and its intensity) of partial analytical indicators on the synthetic indicator ROE.
Keywords: ROE; DuPont pyramid decomposition; indicator dynamization; functional method; box plot